UTILIZATION OF TETANUS TOXOID VACCINATION AND ASSOCIATED FACTORS AMONG WOMEN OF REPRODUCTIVE AGE IN LIRA CITY, NORTHERN UGANDA. ACROSS-SECTIONAL STUDY. - Turyagumanawe, Mathias; Abeja, Christine Joy; Kayizzi, Julius; Modi, Derick (SJ Insights, 2024)
Background Tetanus is a fatal disease caused by Clostridium Tetani. It affects women during pregnancy and 6 weeks postpartum and their neonates in the first 28 days of life who were not protected by the TT vaccine. Africa contributes 44%of global deaths due to tetanus and Uganda with neonatal mortality due to tetanus at 0.65/100000. Tetanus toxoid vaccination is evident in protecting against tetanus disease by receiving 5 doses for lifelong protection. Methodology A cross-section study employing the quantitative method of data collection was done among 151 mothers attending ANC at Ober HCIV who were selected through simple random sampling. Data was entered, double-checked, and cleaned using Statistical Package for Social Sciences (SPSS) version 23 for analysis. Results The response rate was 100%. The level of TT utilization was 58.3% as 41.7% have never received any dose, TTV1- 25.8%, TTV2- 15.2%, TTV3- 8.6%, TTV4- 6.6% and TTV5-2.6%. However, associated factors included the husband’s education level, Family monthly income, exposure to mass media, partner involvement, number of antenatal visits, Place of delivery, Modern family planning use, time travel to the health facility, access to TTV, TT vaccination outreaches in communities and the level of knowledge on TT vaccination utilization. Conclusion Utilization of TT vaccination is very low at 58.5% according to the WHO national target of 90%. Attending antenatal care at least 4 times, having access to TT vaccines, and having good knowledge regarding TT vaccination are significant associations for the utilization of TT vaccination among women of reproductive age group. Recommendation Midwives and Nurses should endeavor to sensitize women of reproductive age and their husbands or next of kin about the importance of utilizing and completing vaccination schedules about maternal and neonatal tetanus.